A laparoscopic management of Swyer syndrome in a woman with pure 46XY gonads and hypoplastic dysgenesis-a rare presentation - Sathyamurthy, Kaavya; Moideen, Nilufer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Swyer syndrome is also known as complete/pure gonadal dysgenesis & is associated with an absence of testicular differentiation in a phenotypic female with a 46, XY karyotype. A 23-year-old married girl had come with complaints of primary infertility. She was averagely built & nourished. She had well developed secondary sexual characteristics like breast development, axillary hairs, and pubic hairs (Tanners stage 4) secondary to receiving HRT for getting menses. External genitalia was of female type. Karyotype showed genotype of 46, XY. Magnetic resonance imaging revealed hypoplastic uterus with rudimentary fallopian tubes , and fibrotic gonad like tissue. A diagnosis of Swyer syndrome was made. The patient was started on hormonal replacement therapy. Dysgenetic streak gonads were removed laparoscopically . Pathologic examination revealed seminiferous tubules ,rete testis & epididymis without evidence of malignant transformation. The patient tolerated the procedure well . Thus laparoscopic prophylactic gonadectomy revealed to be an economical ,straightforward and simple procedure in this patient & risk of neoplasia could be prevented.